Filsafat Inovasi dan Kreativitas Pendidikan Islam di Era Digital - Lailatul Maskhuroh; Abdul Haris (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2022)
Islamic education which has a comprehensive task in internalizing values ??also has the task of preparing students to have skills according to the environment in which they will live later. Technological developments that reached the 4.0 era in this era are also required to prepare software to study this, one of which is a new discipline of philosophy and creativity in Islamic education in the digital era. , philosophy, the characteristics of the philosophy of innovation and creativity of Islamic education in the digital era as well as targeted and answered objects and their areas in the world of education. Because innovation and creativity itself is indeed human nature to be able to always adapt in the midst of an education that is always dynamic. Finally, Islamic education has indicators hereafter. theof resiliencedevelop it (knowledge, wealth, position).